Trend of Da’wah Bil Hal in Industrial Society: A Case Study of PT PLN Purwokerto - Musmuallim, Musmuallim; Baedowi, Muhamad; Tsani, M Happy Nur (Matan : Journal of Islam and Muslim Society, 2024)
The implementation of da’wah can be realized in various places, including the workplace. Da’wah bil hal can be implemented in industrial society according to the rhythm of the work done. In general, da’wah is categorized into two: da’wah bi al-lisan (with oral) and da’wah bi al-hal (with action). The practice of da’wah directly with action (bi al-hal) is no less exciting and widely carried out as a social movement of Islamic da'wah. The form carried out is philanthropy-based and prioritizes generosity and concern for others. This study aims to obtain information about the trend (modern style) of da’wah carried out by PT PLN (Persero) UP3 Purwokerto. Elaborate further on modern da’wah activities as an alternative to the development of da’wah following changes in industrial society. The results of this research can be used as a model or format of modern da’wah for the industrial community, especially players in the industrial world (companies), both government-owned and individual-owned or group-owned (private). Changes in modern society in the industrial world can be balanced with da’wah bil hal, namely by doing various charities following the ability as a worker at work.